EFEKTIVITAS PENERAPAN PASAL 171 KOMPILASI HUKUM ISLAM TENTANG PENGANGKATAN ANAK DI KECAMATAN SUNGAI MANAU KABUPATEN MERANGIN: KAJIAN ATAS WEWENANG PENGADILAN AGAMA - Huda, Itmam (Sosio Akademika, 2025)
This study aims to analyze the effectiveness of the implementation of Article 171 of the Compilation of Islamic Law concerning child adoption in Sungai Manau District. The results of the study show that the application of this law has not been effective in dealing with the problem of child adoption, where the local community still prioritizes the process of adopting children in a customary manner through family agreements and handovers, without involving legal proceedings in court. Although most of the residents of Sungai Manau District are Muslims, understanding of the provisions of Article 171 of the KHI is still low, and the lack of legal sanctions is one of the main factors that cause the high level of non-formal or illegal child adoption. This study uses an empirical juridical approach and finds that child adoption in this region is influenced by several factors, such as couples who have no children or only have children of a certain gender. According to Islamic law, the adoption of a child does not sever the blood relationship with the biological parents, does not change the inheritance status, and the adopted child cannot officially use the name of the adoptive parent. This study emphasizes the importance of stricter law enforcement and education to the public to increase awareness of the importance of child adoption in accordance with legal procedures.